A study of teeth status and oral health related quality of life among elderly in bangladesh - Sumaiya Zabin Eusuf Zai (2018)
Background: This cross sectional study aimed to compare the differences of means score of oral health related quality of life by OHIP-14 among teeth status, general characteristics and daily oral practices among elderly at Purbagram village, Bangladesh. Materials and Methods: A total of 172 elderly about and over 60 years were selected by accidental sampling from Purbagram village. Dental examination to assess teeth status was conducted. Short form of OHIP-14 questionnaire was applied to collect data by interview. Statistics were presented in number and percentage, mean, median, standard deviation, students T-test and ANOVA. Results: The result of the study revealed that more than half of the respondents had 20-28 good teeth (61.4%). Very few of the respondents wear denture (1.7%). More than half of the respondents never brushed their teeth in the morning (64.5%). One-third of the respondents used tooth paste (34.3%). Less than one-third of the respondents were used to smoke regularly (27.9%) Half of the respondents always took betel quid (50.9%). overall mean score of OHIP-14 of the respondents was 22.33 ± 11.29(SD), highest percentage was the item number 7 (poor diet) followed by item number 2 (worsened taste) and item number 4(Discomfort eating food). Only 1.2% of the respondents reported item number 4 very often (inability in function). Item number 14 reported as never more frequently (53.5%) followed by item number 1 (trouble pronouncing words, 52.9%) and 10 (Embarrassment, 52.9%) followed by item number 5 (Feeling self-conscious, 47.1%). Conclusion: The result shows that the mean score of OHIP-14 among the respondents who have 1-19 teeth were higher than who have 20-28 teeth. Elderly with 20-28 teeth had lowest means score of OHIP-14 with the best quality of life related to oral health compare to others. © 2013 Japan International Cultural Exchange Foundation and Japan Health Sciences University.